THE EFFECTIVENESS OF CASE-BASED LEARNING FOR PHYSIOLOGY PRACTICUM SESSION - Wijaya, Diani Puspa; Nurmasitoh, Titis; Pramaningtyas, Miranti Dewi (Universitas Gadjah Mada, 2023)
Background: Basic science laboratory practicum is intended to help improve theachievement of block material. The practical implementation that was applied previously seemed very theoretical. Students find it challenging to associate laboratory practicum's topics with processes that occur in the human body, clinical process, and associate with other material in blocks. The problem has an impact on the score of the pretest and the interest of students in following the laboratory practicum. Physiology laboratory practicum with the method of case-based learning (CBL) is expected to increase the graduation of the pretest and interest of students in following the practicum so that it is expected to improve mastery of the material and link the subject to the real conditions in everyday life. This study aims to determine whether there is an increase in pretest score and student interest in physiology practicum using the CBL method.Methods: The method used in this study is the application of case-based learning inphysiology practicum. After that, the pretest results were analyzed by comparing the control and treatment groups. After completion of the laboratory practicum, the students' perceptions of laboratory practicum with CBL through questionnaires and focus group discussion (FGD) to laboratory practicum participants were completed.Results: The results of the analysis show that the physiological pretest scores ofstudents using the case-based learning method and the addition of local genius material are higher than those who do not use this method (p = 0.00 for blocks 1.4 and 1.6, and p = 0, 03 for block 1.5). Practicum physiology with CBL is attractive for students. In addition, making students better prepared and better understand the material being practiced, and can apply physiological material to the context of everyday life.Conclusion: CBL can be used to increase the effectiveness of physiology learning,especially by increasing student activeness in the learning process, both during preparation before laboratory practicum and also on laboratory practicum process.